Ortodontik Interseptif untuk Penyimpangan Arah Sagital - Krisnawati Krisnawati (Faculty of Dentistry, Universitas Indonesia, 2015)
Early correction procedure frequently used to overcome psycho and physical defects suffered from dental and skeletal disharmonies. THe early correction procedures regarded as an Interceptive Orthodontic due to its advantages such as better efficiency in active treatment, prevent relapse and minimize painful during treatment. Many types of malocclusion e.g. cross bite, mandibular prognathism or retrognathism and malocclusion on cleft lip and palate patients should be treated earlier through this procedure. The aim of this paper is to reveal the importance of Interceptive Orthodontics in treating sagital anomalies.